Framing the Boy Problem in the Early Twentieth Century: The Willie Doherty Murder of 1902 - Marquis, Greg (Urban History Review / Revue d'histoire urbaine, 2018)
In 1902 three teenagers visited a public park in Saint John, New Brunswick. Three days later one of them was found shot to death. This case study of the murder of Willie Doherty and the trials of Frank Higgins and Fred Goodspeed examines how a critical event crystalized the justice system, social reform, and press understandings of the boy problem in one community at the turn of the twentieth century. The case suggested, in the case of working-class youth, the existence of a semi-autonomous “boys world” that operated beyond the reach of adults, including the police. Reformers were as likely to blame environmental influences such as poor parenting, popular culture such as dime novels, or socio-economic deprivation, as they were the anti-social personality traits of delinquents. The study also explores the degree of freedom enjoyed by children and youth in the turn-of-the-century industrial city.